Maxillary sinus elevation surgery with chronos and autogenous bone graft: Analysis of histometric and volumetric changes - Pereira, Rodrigo dos Santos [UNESP]; Boos, Fernanda Brasil Jorge Daura [UNESP]; Gorla, Luis Fernado [UNESP]; Garcia, Idelmo Rangel [UNESP]; Okamoto, Roberta [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Quintessence Publishing, 2016)
The aim of this study was to compare the bone resorption rate and histometry of ChronOS, a beta-tricalcium phosphate (β-TCP), mixed with autogenous bone grafts (1:1) with that of autogenous bone grafts alone in maxillary sinus elevation surgery. A total of 12 maxillary sinuses were grafted with an autogenous bone graft (control group) and 9 with ChronOS mixed with an autogenous bone graft (test group). Postoperative cone beam computed tomography (CBCT) was used to measure the initial graft volume after 15 days (T1), and 6 months later another CBCT scan was performed to evaluate the final graft volume (T2) and determine the graft resorption rate. The resorption outcomes were 45.7% ± 18.6% in the control group and 38.3% ± 16.6% in the test group (P = .17); the bone formation rate was 38.6% ± 10.5% in the control group and 25.4% ± 6.4% in the test group (P = .001). ChronOS mixed with autogenous bone graft demonstrated a resorption rate similar to that of the autogenous bone graft but with a difference in bone formation after 6 months.